PENGARUH PROMOSI JABATAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA HOTEL PATRA CONVENTION SEMARANG - KOESTANTO, DJOKO (Gemawisata: Jurnal Ilmiah Pariwisata, 2012)
Employee satisfaction is one important factor to be a concern for the company in an effort to stimulate employees to work optimally. Employee satisfaction in working in a company strongly influence attitudes in rneiaksanakan duties and expectations. Compensation and Promotions are all factors that can affect job satisfaction for employees to work at a company. Application of compensation imposed in Semarang Convention Hotel Patra felt employees are still far from expected and in addition the company has not set out the conditions for promotion to be known by employees so that employees are motivated to show the work performance as well as recognition of the capabilities and potential employees. Based on this background, the problem in this study is how far the influence of compensation and promotion of employee satisfaction in Hotel Patra Semarang Convention. This study uses the theory of human resource management related to compensation, promotion, job satisfaction and this research aims to determine the effect of compensation and promotion of employee satisfaction on onvention Patra Hotel Semarang. In addition, this study also aims to determine the dominant influence between compensation and promotion of employee satisfaction.Â Key Word: Compensation, Promotion and Job SatisfactionÂ